Impacts of limestone and nitrogen top dressing application on the potassium content in the soil profile and marandu-grass leaf concentration - Balieiro Neto, Geraldo; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP] (Sociedade Brasileira de Zootecnia, 2009)
Objetivou-se avaliar os efeitos de nitrogênio (0, 100, 200, 300 e 400 kg/ha.ano), com ou sem aplicação de calcário dolomítico em cobertura, sobre o teor de potássio (K) do solo nas profundidades de 0 a 5; 5 a 10; e 10 a 20 cm e a concentração de potássio na planta. O experimento foi realizado em Latossolo Vermelho distroférrico de relevo suavemente ondulado, disposto em esquema fatorial 5 × 2, em blocos casualizados, com quatro repetições. A adubação nitrogenada promoveu aumento linear na concentração de potássio na planta e no teor desse mineral na camada de 0 a 5 cm do solo. Ocorreu efeito de inibição competitiva entre a absorção de potássio e cálcio e entre potássio e magnésio. Embora uma fração significativa de potássio retorne à camada superficial do solo pelo resíduo de forragem, em decorrência da maior produção de massa, o aumento da concentração de potássio na planta nas mais altas doses de nitrogênio comprova a importância do suprimento de potássio para a planta, por intensificar a massa de forragem.

The objective of this experiment was to evaluate the effects of nitrogen doses (0, 100, 200, 300, and 400 kg ha-1 year-1), with or without dolomitic lime covering application, on the potassium (K) soil content at depths varying form 0 to 5, 5 to 10, and 10 to 20 cm, and the potassium concentration in the plant. The experiment was carried out in a rhodic ferralsol with a slightly rolling relief, in a 5 × 2 factorial arrangement, in a complete randomized block design, with four replications. Nitrogenated fertilization caused a linear increase in the potassium concentration in the plant and also in the mineral content in the 0-5 cm soil layer. An effect of competitive inhibition occurred between the potassium and calcium absorption, and potassium and magnesium absorption. Although a significant fraction of potassium returned to the soil surface layer through the forage residue due to the increase in dry matter production caused by nitrogenated fertilization, the increase in the potassium concentration in the plant due to the doses of nitrogen demonstrated the importance of considering the potassium supply to the plant, when the forage mass is intensified through nitrogenated fertilization.
Impactos da aplicação de calcário e nitrogênio em cobertura no teor de potássio no perfil do solo e na concentração foliar do capim-marandu
Keywords: Mineral nutrition; Soil fertility; Urea; Urochloa; Solos - Fertilidade; Nutrição mineral; Uréia; Urochloa